Musical Hallucinations Treated with Acetylcholinesterase Inhibitors - Blom, Jan Dirk; Coebergh, Jan Adriaan F.; Lauw, René; Sommer, Iris E. C. (Frontiers in Psychiatry, 2015)
Musical hallucinations are relatively rare auditory percepts which, due to their intrusive nature and the accompanying fear of impending mental decline, tend to cause significant distress and impairment. Although their etiology and pathophysiology appear to be heterogeneous and no evidence-based treatment methods are available, case reports indicate that acetylcholinesterase inhibitors may yield positive results in patients with comorbid hearing loss. We present two female patients (aged 76 and 78 years) both of whom suffered from hearing impairment and practically incessant musical hallucinations. Both patients were successfully treated with the acetylcholinesterase inhibitor rivastigmine. Based on these two case descriptions and an overview of studies describing the use of acetylcholinesterase inhibitors in similar patients, we discuss possible mechanisms and propose further research on the use of acetylcholinesterase inhibitors for musical hallucinations experienced in concordance with hearing loss.